2019
DOI: 10.1186/s40644-019-0216-6
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of hepatocellular carcinoma response to 90Yttrium radioembolization using volumetric ADC histogram quantification: preliminary results

Abstract: Purpose To assess the predictive value of volumetric apparent diffusion coefficient (vADC) histogram quantification obtained before and 6 weeks (6w) post-treatment for assessment of hepatocellular carcinoma (HCC) response to 90 Yttrium radioembolization (RE). Methods In this retrospective study, 22 patients (M/F 15/7, mean age 65y) who underwent lobar RE were included between October 2013 and November 2014. All patients underwent routine liver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…All of these characteristics displayed significant spatial differences. Histogram analysis (i.e., first-order radiomics) is an approach that captures the distribution of individual voxel value intensities that may quantify tumor heterogeneity in a routine MRI volume of interest (VOI), and some tumor studies have suggested that such analyses indeed assisted with the evaluation of diagnoses, biologic aggressiveness and prognoses ( 25 28 ). However, the performance gains of models built with first-order statistics are relatively limited when the spatial variations between voxels are not considered.…”
Section: Discussionmentioning
confidence: 99%
“…All of these characteristics displayed significant spatial differences. Histogram analysis (i.e., first-order radiomics) is an approach that captures the distribution of individual voxel value intensities that may quantify tumor heterogeneity in a routine MRI volume of interest (VOI), and some tumor studies have suggested that such analyses indeed assisted with the evaluation of diagnoses, biologic aggressiveness and prognoses ( 25 28 ). However, the performance gains of models built with first-order statistics are relatively limited when the spatial variations between voxels are not considered.…”
Section: Discussionmentioning
confidence: 99%
“…This situation might be the reason for the missing correlation. Nevertheless, despite some studies reporting a correlation between lower ADC values with early recurrence after liver transplantation [10] or SIRT [29], and lower OS after TACE or SIRT [30], all of these studies are retrospective single-centre studies; and other studies have reported no such correlation [15]. HCC has mostly a heterogeneous intratumoral architecture, especially in large lesions.…”
Section: Discussionmentioning
confidence: 99%
“…There is ample research available focusing on potential imaging biomarkers in the early postinterventional period to predict overall survival (OS) and progression free survival (PFS) [ [14] , [15] , [16] , [17] , [18] , [19] , [20] , [26] , [27] ]. With all these methods, however, TARE (or Transarterial Chemoembolization) has already been performed by the time when a statement can be made if the treatment was likely to be successful or not.…”
Section: Discussionmentioning
confidence: 99%